Characteristic analysis of magnetorheological fluid porous fabric composite with a novel constitute model. (1st February 2023) - Li, Pingyang; Dong, Xiaomin; Wang, Kaixiang; Ran, Jinchao; Yang, Baolin
Abstract: As a novel material, magnetorheological fluid porous fabric composite (MRF-PF) has not been further analyzed and modeled. In this paper, mechanical properties of MRF-PF are analyzed quantitatively and qualitatively with a novel constitute model. Considering the wall slip, viscoelasticity and internal porous network of MRF-PF, a constitute model of MRF-PF is derived firstly which can describe the performance precisely. According to experimental results, mechanical properties of MRF-PF are different from conventional MRF. Shear stress τ decreases first, then increases slowly at off-state. Under low magnetic field, shear stress τ presents the opposite variation. It increases at first, and then decreases rapidly. With the further increase of magnetic field, Shear stress τ increases dramatically at high shear rate. This effect is determined by the internal porous network and absorption degree of MRF-PF. A possible flow mechanism of MRF-PF has been proposed. Comparing with different types of MRF-PFs, pre-immersed MRF-PF without relative rotation has a better performance. The maximum shear stress can reach as high as 62.35 kPa with an increase of 22.37% under the magnetic field of 0.7 T. The corresponding dynamic yield stress τ y increases to 55.18 kPa with an increase of 26.6%. What is more, internal porous network can support the particle chains to reinforce the shear-resistance property. The shear thinning effect of MRF-PF can be improved significantly. However, MR effect of MRF-PF decreases largely. These attractive mechanical properties make MRF-PF a potential choice for critical engineering applications.